The Influence of Consanguinity on Familial Clefting Among Palestinians. (September 2019) - Saeed, Omar B.; Moore, Meredith Grogan; Zawahrah, H.; Tayem, M.; Kavoosi, Tazheh; van Aalst, John A.
Introduction: Orofacial clefts (OFC) are the most common congenital craniofacial anomaly. The relationship between intermarriage (consanguinity) and positive family history for OFC is not well described. Consanguinity rates in developed countries are <1% but are considerably higher in the Middle East (45%). Familial clefting rates in developed countries are under 20% but in the Middle East are reported at 30% or higher. Objective: To determine OFC demographics and to clarify the relationship between consanguinity and familial clefting among Palestinians. Design: The Palestinian Congenial Anomalies Database is based on a 700-question survey administered to mothers of children with congenital anomalies. Orofacial clefts were diagnosed in 540 children. All demographic data were analyzed using χ 2 tests with a level of significance at α < .05. Results: Demographics for OFC among Palestinians were similar to other published reports. Overall consanguinity rate was 53% and familial clefting rate was 49%. Parental rates of consanguinity were significantly different for patients with cleft palate. Patients with consanguineous parents had a higher rate of positive family history of clefting (67%). Recurrence of clefts in siblings was significantly higher among those born to consanguineous parents (73%) when compared to nonconsanguineous parents. Conclusion: Consanguinity rates for Palestinians with OFC were higher than those reported in the Middle East. Familial clefting and sibling recurrence rates were also higher than expected. The risk of OFC may be mitigated with improved education about anticipated genetic consequences of consanguinity in high-risk populations such as the southern West Bank.